Representasi Imigran Timur dalam Film The Visitor - Analisa Dwimas Priyantari; Akhmad Kautsar Fattah (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
The film is a depiction of meaning made in visual form. The study aims to see the representation of eastern immigrants in The Visitor. Motivated by the 9/11 event which took place in New York, the United States that made a negative stigma of eastern immigrants, the film tells the friendship between Western and Eastern people. Researchers use Dramatistic Pentad analysis to see how Eastern immigrant representations are displayed using act, scene, agent, agency, and purpose analyses. Researchers also used the theory of Orientalism by Edward Said to see Eastern and Western depictions. Researchers examined the six scenes in The Visitor film, using qualitative data analysis. The results showed that the film gave a positive image of eastern immigrants to change the negative perception of Western peoples towards Muslims.